Mining megaprojects in Mozambique and the compulsury resettlement: case of Nacala-à-Velha district, Nampula province - Vanito Frei; Nélio Manuel (Entre-Lugar, 2021)
The productive (re) structuring of capital, which has been implemented in Mozambique, through the territorialization of mining megaprojects, has influenced the compulsory displacement of local communities, causing profound changes in the social and economic way of life of these communities. It is this concern that permeates this study, whose objective is to analyze the socio-territorial implications of the construction of the ferro-port terminal in the resettled communities in the district of Nacala-à-Velha, province of Nampula. Thus, for the analysis of the research object, the study privileged bibliographic and documentary research. Data collection was carried out using interview techniques and questionnaires, based on direct observations made during fieldwork in resettled communities in Nacala-à-Velha. The results obtained allowed us to understand that Vale's resettlement programs in the Nacala-à-Velha district are part of the context of the emergence of transnational appropriations of land or landgrabbing, which provide for the granting of vast portions of land to foreign investors, and, therefore, the expropriation of local communities to remote, infertile regions, lacking access to natural goods such as: drinking water, agricultural inputs, schools, hospitals and markets, thus increasing the lack of employment and food insecurity within the communities. . In short, forced resettlement causes a territorial disruption of communities, which generally leads to negative effects and is difficult to compensate or mitigate.